2015
DOI: 10.3109/10520295.2015.1021380
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in rat pancreas and skeletal muscle associated with high fat diet induced insulin resistance

Abstract: The effects of a high fat diet on the development of diabetes mellitus, insulin resistance and secretion have been widely investigated. We investigated the effects of a high fat diet on the pancreas and skeletal muscle of normal rats to explore diet-induced insulin resistance mechanisms. Forty-four male Wistar rats were divided into six groups: a control group fed standard chow, a group fed a 45% fat diet and a group fed a 60% fat diet for 3 weeks to measure acute effects; an additional three groups were fed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
7
12
0
Order By: Relevance
“…In the histopathological aspect of pancreatic sections, our results were similar to other reports (Gulen, Bagla, Yavuz, & Hismiogullari, 2015;Vieira et al, 2013;Yan, Li, Meng, Ren, & Kou, 2006). Several studies reported that the hypertrophy of β cell mass is necessary due to the increase in metabolic demand in IR status induced by glucolipotoxicity.…”
Section: Concerning Glucose Dysregulation Several Studies Concur Withsupporting
confidence: 91%
“…In the histopathological aspect of pancreatic sections, our results were similar to other reports (Gulen, Bagla, Yavuz, & Hismiogullari, 2015;Vieira et al, 2013;Yan, Li, Meng, Ren, & Kou, 2006). Several studies reported that the hypertrophy of β cell mass is necessary due to the increase in metabolic demand in IR status induced by glucolipotoxicity.…”
Section: Concerning Glucose Dysregulation Several Studies Concur Withsupporting
confidence: 91%
“…The underlying mechanisms behind the observed association in NODAP are not fully understood, but one possible mechanism is increased IPFD due to elevated triglycerides [46,47]. This is supported by an animal study suggesting that a high-fat diet induces both interlobular and intralobular fat deposition [48]. Although there is little evidence on the role of fat in insulin sensitivity in the post-pancreatitis setting, a previous study showed a strong positive association between the levels of serum triglycerides and IPFD in non-selected individuals after AP (which, in theory, might have been attributed to a high BMI) [49].…”
Section: Discussionmentioning
confidence: 78%
“…The obesity epidemic has become a major global health burden due to relating comorbidities such as hyperglycemia, insulin resistance, and diabetes mellitus (type 2 diabetes [T2DM]) (Ickin Gulen et al, 2015; Wanchai et al, 2018). Several studies have so far demonstrated that long term high‐fat diet (HF) consumption induces not only obesity and insulin resistance but also histopathological alterations of the pancreas, which closely resemble early phases of T2DM (Ickin Gulen et al, 2015; Swe et al, 2019). In the initial phases of T2DM, pancreatic β‐cells adapt to the increase in insulin command by expanding β‐cell mass, leading to enlarged insulin production during obesity and insulin resistance (Bernal‐Mizrachi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%